Software testing and quality assurance : - Naik, Kshirasagar (John Wiley & Sons, 2008)
Software Testing and Quality Assurance: Theory and Practice equips readers with a solid understanding of: Practices that support the production of quality software Software testing techniques. Life-cycle models for requirements, defects, test cases, and test results. Process models for units, integration, system, and acceptance testing. How to build test teams, including recruiting and retaining test engineers. Quality Models, Capability Maturity Model, Testing Maturity Model, and Test Process Improvement Model